What more can Software Development Learn from Agile Manufacturing? Some Pointers on the 20th Anniversary of the Agile Manifesto - Kakar, Ashish (Journal of the Southern Association for Information Systems, 2023)
The concept of agility originated in manufacturing and was later adopted by the software development discipline. In this article we argue that in the process some important aspects of the agility theory have been either ignored or misinterpreted. A historical review of the evolving paradigms and practices in software development and manufacturing on the 20th anniversary of the Agile Manifesto (2001) suggests that if the ideas and principles underlying agility are faithfully implemented it would lead to significant improvement in the software development process.